An aqueous pomegranate seed extract ameliorates oxidative stress of human hepatoma HepG2 cells. (3rd December 2013) - Navarro, Marta; Amigo‐Benavent, Miryam; Mesias, Marta; Baeza, Gema; Gökmen, Vural; Bravo, Laura; Morales, Francisco J
Abstract BACKGROUND Aqueous pomegranate seed extract (PSE), a by‐product of the pomegranate juice industry, was recently identified as a potential antiglycative ingredient. Ellagic acid was proposed as the major polyphenol responsible for the antiglycative activity as exerted in in vitro models. However, there is no information on safety aspects of this extract in biological systems before its application as ingredient. The cytotoxicity of PSE (1–100 µg mL−1) was evaluated by determining its effect on cell viability and redox status of cultured HepG2 cells. The protective effect of the PSE against oxidative stress induced by tert‐butyl hydroperoxide (t‐BOOH) was also investigated. RESULTS No changes in cell integrity or intrinsic antioxidant status resulted from a direct treatment with aqueous PSE, even at high dosage. In addition, reactive oxygen species (ROS) induced by t‐BOOH were reduced by 21% when cells were pretreated with 100 µg mL−1 of aqueous PSE at 180 min. The range of concentrations investigated was effective in decreasing the ROS formation but not in a dose‐dependent manner. CONCLUSION Aqueous pomegranate seed extract enhances human hepatoma cells integrity and resistance to cope with a stressful situation at concentration up to 100 µg mL−1. © 2013 Society of Chemical Industry